2015
DOI: 10.1134/s1063782615060238
|View full text |Cite
|
Sign up to set email alerts
|

Linear chains of Ge/Si quantum dots grown on a prepatterned surface formed by ion irradiation

Abstract: The growth of Ge nanoclusters on a prepatterned Si (100) surface formed by imprint lithography in combination with subsequent irradiation with Ge + ions is studied. The prepatterned surface presents a sys tem of parallel 10 nm wide grooves repeating with a period of 180 nm. Irradiation of the substrate was con ducted at two temperatures, room temperature (cold irradiation) and 400°C (hot irradiation). It is shown that, during epitaxy (550-700°C), the residual radiation defects located in the bulk under the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…[10] that in a Ge/Si nanosystem with germanium QDs in the integral of average QD radii (6.4 eV, which was observed under experimental conditions up to room temperature. [1][2][3]7] Let us assume that the distances D between the surfaces of the QDs will be the same in the entire linear chain of germanium QDs on the substrate of the silicon matrix. [3,7] As a result, of electron tunneling through the potential barrier U(x) (6)- (8), which separates QDs, the exciton states E ex ðaÞ are splitted, forming a zone of localized electron states in a linear germanium QD chain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] that in a Ge/Si nanosystem with germanium QDs in the integral of average QD radii (6.4 eV, which was observed under experimental conditions up to room temperature. [1][2][3]7] Let us assume that the distances D between the surfaces of the QDs will be the same in the entire linear chain of germanium QDs on the substrate of the silicon matrix. [3,7] As a result, of electron tunneling through the potential barrier U(x) (6)- (8), which separates QDs, the exciton states E ex ðaÞ are splitted, forming a zone of localized electron states in a linear germanium QD chain.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that in these nanostructures a photoluminescence signal in the infrared spectral region (0.20-1.14) eV was observed up to room temperature. [1][2][3][4][5][6][7] At low concentrations N QDs of germanium, when in linear chains, the average distance (%N À1/3 ) between the surfaces of the QD significantly exceeds the Bohr radius of the electron (a e ¼ 0.63 nm) in the silicon matrix, that is a e N 1=3 ( 1 (1) the interaction between QDs can be neglected. The optical properties of such nanosystems were mainly determined by the energy spectra of electrons and holes localized near the surface of single germanium QDs grown in a silicon matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative estimation of the QD size corresponding to various exciton states can be carried out using the real nanosystem [1-3] containing the germanium QD with a radius a and permittivity  2  16. 3 , r e and r h are electron and hole distances from the QD centre [4,5]. In nanosystem, the main electronic level is located in silicon ma-trix, and the main hole level is in the QD.…”
Section: The Energy Spectrum Of a Spatially Indirect Exciton In A Nanmentioning
confidence: 99%
“…In Ref. [3], heterostructures, which are linear germanium QD chains on silicon substrates, were obtained using the method of electron beam lithography. The average radii of QD of germanium did not exceed 30 nm.…”
Section: Introductionmentioning
confidence: 99%